Developmental differences in addition strategies: a comparison of mathematically disabled and mathematically normal children - Ostad, Snorre A. (British journal of educational psychology, 1997)
Background. Several studies concerned with task‐specific strategies in addition have suggested that, when compared with the performance of mathematically normal peers (MN pupils), the performance of mathematically disabled pupils (MD pupils) is characterised by frequent use of inefficient problem‐solving strategies. These studies, however, have focused more or less exclusively on single age‐groups and on the youngest age‐groups in particular. What characterises strategy use, as this develops year by year during the primary school stage, has not been adequately studied. Aims. The major purpose of the present study was to investigate the character and extent of differences between the MD pupils and the MN pupils as reflected in the use of task‐specific strategies for solving elementary addition problems as the pupils move up through primary school, i.e., from grade 1 to grade 7. Particular concern was with the variability within the groups of MD pupils, especially in light of the general literature showing substantial heterogeneity in the performance characteristics of the mathematically less able children. Sample. The sample included 32 MD pupils in grade 1, 33 MD pupils in grade 3, 36 MD pupils in grade 5 and a corresponding number of MN pupils in each of the grades. Methods. The pupils were asked to solve 28 single‐digit addition problems on two different occasions separated by an interval of two years. The task‐specific strategies used by the pupils were recorded on a ‘trial‐by‐trial basis' and were classified as defined single variants of backup strategies and retrieval strategies, respectively. Results. The pattern of development as it emerged in a longitudinal perspective in the present study showed the mathematically disabled pupils as being characterised by: (a) use of backup strategies only, (b) use of the most primary backup strategies, (c) small degree of variation in the use of strategy variants and, (d) limited degree of change in the use of strategies from year to year throughout the primary school. Conclusions. Compared with the mathematically normal pupils, the mathematically disabled exhibited a divergent pattern of development, with unexpectedly little variability within the group itself.